2019
DOI: 10.1177/0145445519890261
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Training with Adolescents in a Residential Juvenile Facility

Abstract: For individuals receiving treatment in residential juvenile facilities, the inability to tolerate typical but unpleasant stimulus events may manifest in aggressive behavior toward staff or other residents. Such behaviors can lead to loss of privileges, interfere with other treatments, and contribute to negative staff-student relationships. As a procedure, tolerance training (TT) involves systematically increasing the duration of exposure to an undesired stimulus event or situation. The current study evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…When ordered to stay at home, children must do so, even if the home environment is cramped and avoiding others is impossible. To address these situations, behavior analysts should teach tolerance to nonpreferred activities and situations using graduated exposure and reinforcement (e.g., Cook, Rapp, & Schulze, 2015;O'Rourke, Richling, Brogan, McDougale, & Rapp, 2019). Increasing rates of, lengthening durations of, or shortening delays to reinforcement improve the efficiency and effectiveness of graduated exposure to nonpreferred activities and situations.…”
Section: Increasing Positive Reinforcementmentioning
confidence: 99%
“…When ordered to stay at home, children must do so, even if the home environment is cramped and avoiding others is impossible. To address these situations, behavior analysts should teach tolerance to nonpreferred activities and situations using graduated exposure and reinforcement (e.g., Cook, Rapp, & Schulze, 2015;O'Rourke, Richling, Brogan, McDougale, & Rapp, 2019). Increasing rates of, lengthening durations of, or shortening delays to reinforcement improve the efficiency and effectiveness of graduated exposure to nonpreferred activities and situations.…”
Section: Increasing Positive Reinforcementmentioning
confidence: 99%
“…Neil ( 2011 ) suggested compliant (or cooperative) behavior could be either “active” or “passive.” In particular, Neil argued active compliance requires an individual to emit a specific response following an instructor’s request, whereas passive compliance does not. To this end, O’Rourke et al ( 2021 ) adapted an intervention originally designed by Ghaemmaghami et al ( 2016 ) to increase students’ passive compliance 5 or “tolerance skills” to aversive stimulus events. Facility staff members reported students engaged in disruptive behaviors (e.g., negotiating, property destruction, aggression) when they were either denied access to preferred activities or instructed to “deal with” nonpreferred situations (e.g., periods of low staff attention).…”
Section: Behavioral Interventions For Individual Studentsmentioning
confidence: 99%
“…It is important to note that O’Rourke et al ( 2021 ) modified procedures previously applied to individuals diagnosed with autism spectrum disorder (ASD; Cook et al, 2015 ; Rapp et al, 2005 , 2017 ; Ricciardi et al, 2006 ; Schumacher & Rapp, 2011 ). As the cornerstone of tolerance training, O’Rourke et al taught students to request what they wanted when staff members presented a nonpreferred scenario and thereafter to tolerate situations in which their requests were denied (see Ghaemmaghami et al, 2016 ).…”
Section: Behavioral Interventions For Individual Studentsmentioning
confidence: 99%
“…Therefore, this review focuses on the 10 identified intervention research studies aimed at improving the behavior of youth in JCF (see Table 1). Specific to the current systematic review, results of the electronic search resulted in identifying two relevant studies (i.e., Brogan et al, 2017; Edgemon et al, 2020), while the hand search led to the inclusion of another eight studies (i.e., Brogan et al, 2020; Chinnappan et al, 2020; Hamrick et al, 2020; Knight et al, 2019; Lively et al, 2019; McDougale et al, 2019 (two studies in one article); O’Rourke et al, 2020). Overall, included studies came from a small number of research journals, including Behavior Modification ( n = 7), Journal of Applied Behavior Analysis ( n = 1), Criminal Justice and Behavior ( n = 1), and The Journal of Correctional Education ( n = 1)…”
Section: Thematic Coding Processmentioning
confidence: 99%